Representation of Vietnam in 2006:A Comparative Study between Western and Local Media - Thanh, Le Trieu (Bodhi: An Interdisciplinary Journal, 2010)
But, like any frame that delineates a world, the news frame may be considered problematic. The view through a window depends upon whether the window is large or small, has many panes or few, whether the glass is opaque or clear, whether the windows faces a street or a backyard. The unfolding scene also depends upon where one stands, far or near, craning one's neck to the side, or gazing straight ahead, eyes parallel to the wall in which the window is encased" (Gaye Tuchman - Making news: A study in the Construction of Reality, 1978, p.1) DOI: 10.3126/bodhi.v2i1.2864 Bodhi Vol.2(1) 2008 p.64-88